Statehood exercises in Ethiopia and their jurisprudential significance: clarifying normative hurdles and addressing empirical challenges - Afesha, Nigussie; Barrett, Hazel Rose (Regional & federal studies, 2025)
This paper discusses the unconditional right to self-determination claim of ethnic groups under the Federal Democratic Republic of Ethiopia (FDRE) Constitution, and how the demands for statehood have been handled since 2018. Using the Sidama and South-Western Ethiopian Peoples (SWEP) statehood exercise, this paper highlights the main issues and challenges concerning the process of claiming and achieving internal statehood. These include the principles of who has the right to vote in a statehood referendum, the matter of ethnic clustering to claim statehood, protecting the rights of minorities, the challenge of merging geographically distant Nations, Nationalities and Peoples (NNPs) into states, the transfer of power to the new state, and the division of assets and liabilities once a statehood claim is approved. It concludes that whilst the Constitution is flexible and allows for innovation, the Sidama and SWEP experiences demonstrate that it is now time for a review of the Constitution.